Carbon Cloth: In Situ Grown MWCNTs/MXenes Nanocomposites on Carbon Cloth for High‐Performance Flexible Supercapacitors (Adv. Funct. Mater. 47/2020). (18th November 2020) - Li, Hui; Chen, Rui; Ali, Mumtaz; Lee, Haiwon; Ko, Min Jae
Abstract : In article number 2002739, Haiwon Lee, Min Jae Ko, and co‐workers propose a unique 3D interconnected nanocomposite consisting of pristine MXene and multiwall carbon nanotubes (CNTs), which can be applied as active materials in flexible supercapacitors. The in‐situ grown CNTs effectively maintain the hierarchical structure of the MXene and accelerate electron transport in the electrode.